2018
DOI: 10.1186/s13019-018-0761-2
|View full text |Cite
|
Sign up to set email alerts
|

Single stage repair for aortic root aneurysm in a patient with coexisting coarctation incorporating the Cabrol technique: a case report

Abstract: BackgroundA 44 year old man who presented with a history of chest pain and dyspnoea was found to have an aneurysm of the aortic root, aortic valve insufficiency, and coarctation of the aorta.Case presentationThe patient underwent a single stage procedure to treat the aortic root, valve and coarctation with a composite valved conduit and extra-anatomic bypass of the coarctation. The modified Cabrol technique was necessary to attach the coronary buttons due to grossly abnormal anatomy. The patient made a remarka… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…If a median sternotomy is used, it is easier to perform an ascending-to-descending aortic bypass rather than CoA surgical repair. 11 The most frequent complication of extraanatomical bypass is prosthetic deformation, although it has been noted that kinking can be avoided if the prosthesis is laid along the left border of the heart. 17 In this study, multislice computed tomography revealed a huge thrombosis (6.5 сm) in a patient in the first group, extending from the CoA zone to the descending aorta.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…If a median sternotomy is used, it is easier to perform an ascending-to-descending aortic bypass rather than CoA surgical repair. 11 The most frequent complication of extraanatomical bypass is prosthetic deformation, although it has been noted that kinking can be avoided if the prosthesis is laid along the left border of the heart. 17 In this study, multislice computed tomography revealed a huge thrombosis (6.5 сm) in a patient in the first group, extending from the CoA zone to the descending aorta.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, there has been an increase in the number of reports of single-stage procedures for CoA correction with ascending aortic aneurysm repair. 11 Single-stage procedures can be performed using either surgical or transcatheter CoA correction. 12 While transcatheter treatment provides better results in terms of short-term postoperative complications, there is a higher rate of restenosis in the medium term, requiring a second intervention (11% vs.…”
Section: Discussionmentioning
confidence: 99%